Analyze of Teachers’ Hidden Competencies in Muadalah Education Units - M. Abu Jihad Lillah (At-Ta'dib, 2021)
This research is a library research, examining books of ideas of figures about teacher competence in muadalah education units and laws related to teacher competence. This study is purposed to analyze how formulation of teachers’ hidden competences in muadalah education units. While the results of study shows that the formulation of teachers’ competencies in muadalah education units must have professional competence, competence pedagogic, personality competence, and social competence. These competencies are already listed in the Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers. There are also hidden competences, consisting of: sincerity; soul of simplicity; spirit of independence; soul ukhuwwah Islamiyah; and the spirit of freedom, is the center of personality and knowledge related to teacher work performance. This hidden competence contributes greatly to teacher performance, meaning that hidden competence becomes the center of personality, becomes a leverage and a driving force for visible competencies.